2022
DOI: 10.52965/001c.34224
|View full text |Cite
|
Sign up to set email alerts
|

Combination Olanzapine and Samidorphan for the Management of Schizophrenia and Bipolar 1 Disorder in Adults: A Narrative Review

Abstract: Schizophrenia is a debilitating psychotic disorder characterized by positive symptoms such as delusions, hallucinations, and disorganized thoughts, and negative symptoms like lack of effect or motivation. Bipolar 1 disorder (B1D) is a psychiatric illness characterized by recurrent manic episodes in alternation with depressive episodes and interspersed periods of euthymia, ultimately resulting in psychological distress and impairment of daily functioning. Effective treatments are needed for both schizophrenia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 118 publications
0
4
0
Order By: Relevance
“…[26][27][28]30,31 Haddad et al also had documented that OLZSAM exhibited fewer adverse effects than OLZ, and the same has been substantiated by Jawad et al, as they observed that in short-term studies, the addition of the µ-opioid receptor antagonist did not alter the safety profile of the OLZ. 15,20 Interestingly, we observed that the incidences of various adverse events were either high in the OLZ group or the OLZSAM group. In the former group, the incidence of any adverse event and any SAEs was high, though statistically insignificant, while in the latter group, the incidence of somnolence, dry mouth, headache, and drug discontinuation due to adverse events was high, and a statistically significant difference was observed for the incidence of dry mouth (p = 0.01).…”
Section: Events (Especially Weight Gain) the Outcomes Are Based On We...mentioning
confidence: 77%
See 3 more Smart Citations
“…[26][27][28]30,31 Haddad et al also had documented that OLZSAM exhibited fewer adverse effects than OLZ, and the same has been substantiated by Jawad et al, as they observed that in short-term studies, the addition of the µ-opioid receptor antagonist did not alter the safety profile of the OLZ. 15,20 Interestingly, we observed that the incidences of various adverse events were either high in the OLZ group or the OLZSAM group. In the former group, the incidence of any adverse event and any SAEs was high, though statistically insignificant, while in the latter group, the incidence of somnolence, dry mouth, headache, and drug discontinuation due to adverse events was high, and a statistically significant difference was observed for the incidence of dry mouth (p = 0.01).…”
Section: Events (Especially Weight Gain) the Outcomes Are Based On We...mentioning
confidence: 77%
“…This effect culminates from the antagonism of the µ-opioid receptor, inhibiting the mesolimbic reward system responsible for inducing food cravings. 15,39…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations